Determinants of Job Creation in Eleven New EU Member States Evidence from Firm Level Data - Oberhofer, Harald (The World Bank, 2013)
This paper builds on the analysis of job creation developed in World Bank (2013) to provide an empirical investigation of the industry and firm-specific determinants of the job creation process in eleven new European Union (EU11) economies. It relies on the Amadeus dataset of firms during 2002-2009. The main results indicate that during the years prior to the global financial crisis, traditional industries were crucial for the net creation of jobs in EU11. However, traditional industries were the ones most severely affected by the financial crisis. By contrast, services firms were less vulnerable to the economic downturn. At the firm level, small and young firms registered the highest employment growth rates. The empirical results also indicate that more productive firms tended to be less vulnerable to economic downturns. Moreover, the results demonstrate that the perceived quality of the business climate by the EU11 enterprises is correlated with not only the firms' employment growth, but also their productivity. In the post-crisis period, poor business restrictions were negatively associated with the creation of jobs. All these findings hold for the group of high-growth firms that disproportionately accounted for the creation of new jobs in the EU11 economies